TO STUDY THE RISK FACTORS ASSOCIATED WITH METABOLIC SYNDROME IN CORONARY ARTERY DISEASE PATIENTS - KAUR, JASPREET; KAUR, JASWANT; MITTAL, MRIDULA; SINGH, TEJINDER; GUPTA, VISHAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Indians are more likely to develop metabolic syndrome (MetS). The additive predictive value of MetS components for cardiovascular disease is still under debate. The current study aimed to study the risk factors associated with MetS in coronary artery disease (CAD) patients. Methods: This retrospective study was conducted in the Department of Biochemistry in collaboration with the Department of Medicine, Noida International Institute of Medical Sciences, Gautam Buddha Nagar, Up on 100 patients already diagnosed with CAD, attending medicine OPD and IPD. Anthropometric measurements, and estimation of fasting blood glucose, high-density lipoprotein-cholesterol, and triglycerides were done. MetS prevalence was estimated as per the guidelines of NCEP ATP III. Results: In our study, we observed a high incidence of MetS in patients with CAD. MetS was diagnosed, gender-wise distribution resulted in 62% in females and 48% in males. Risk factors for MetS in CAD patients were highly significant with increasing age, sedentary lifestyle, and diabetes. Waist circumference, fasting blood glucose levels, and triacylglycerol were found to have a significant *p<0.001 value with MetS in CAD patients. Conclusions: The current study found a strong link between MetS and its risk factors in CAD patients. Thus, the assessment of MetS and its components might help identify people at a higher risk of advancing CAD in the future. Hence, effective MetS management may significantly reduce morbidity and mortality due to CAD.